Properties of macerated herbal oil - Fahsai Kantawong (2018)
© 2017 The Author(s). Introduction: The addition of herbs into hot sesame oil could increase the oil-pulling efficiency of sesame oil. The aim of present study was to modify the proportion of herbs and sesame oil with the addition of other ingredients including menthol, camphor, and borneol and improve the medicinal properties and the scent of the oil. Methods: Macerated herbal oil was prepared by heat extraction of five species of herbs (Zingiber cassumunar, Zingiber zerumbet, Plantago major Linn, Citrus hystrix, and Amomum biflorum) with hot sesame oil. The study was performed to evaluate the anti-oxidant, anti-inflammatory, and anti-bacterial properties of this macerated herbal oil. Results: Macerated herbal oil was evaluated for antioxidant activity using DPPH and ABTS assays. It was shown that at dilution 1:2 in DMSO, the macerated herbal oil had DPPH and ABTS radical scavenging activities equal to 63% and 22%, respectively. Macerated herbal oil dilution 1:8 in DMSO demonstrated ferric reducing capacity equivalent to ascorbic acid (0.208 μM) and had reducing power equivalent to butylated hydroxytoluene (BHT) 7.41 μg/mL. MTT assay was performed using immortalized human mesenchymal stem cells (HMSCs) as a cell culture model. The result indicated that the cytotoxic concentration of the macerated herbal oil was ≥ 2.5 μL/ mL in complete DMEM. Anti-inflammatory effects were evaluated using the nitrite assay and RT-PCR. It was found that the macerated herbal oil could inhibit nitrite accumulation in culture media. Change in the expression of COX-2, Nrf2, and NF-kB in RT-PCR confirmed the antiinflammatory activity of the macerated herbal oil. Conclusion: It could be concluded that the macerated herbal oil could inhibit nitrite accumulation in culture media, which might be the inhibitory effect of the macerated herbal oil on COX-2 or Nrf2, the downstream modulator of the COX-2 pathway. Further intensive studies are needed for the optimization before bringing this macerated herbal oil into clinical application.